On γ-Clean Rings - Esa, Shaimaa S.; Faris, Hewa S. (Science Journal of University of Zakho, 2017)
In this paper we introduce the concept of -clean ring and we discuss some relations between - clean ring and other rings with explaining by some examples. Also, we give some basic properties of it.
Keywords: γ-clean rings; r-clean rings; clean rings and γ-regular rings; regular rings